Neutrosophic DEMATEL to Prioritize Risk Factors in Teenage Pregnancy Sets - Diego Raúl Bonifaz Díaz; Lotty Rosita Ramírez López; Laura Paola Advendaño Castro (Neutrosophic Sets and Systems, 2020)
Care during pregnancy is a task of high importance for the health system. In Ecuador, special importance has been given to pregnant teenagers. However, there are various factors that influence pregnancy and in many cases it is not possible to prioritize their care. This research aims to develop a model to prioritize the factors that influence teenage pregnancy. The model operates using the neutrosophic DEMATEL method for the study of cause and effect in complex situations. The method implements as a principle the modeling of neutrality using neutrosophic numbers and allows evaluation through the use of linguistic terms, which is a natural form of evaluation for humans.